2020
DOI: 10.1111/jnp.12227
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and motor deficits in older adults with HIV infection: Comparison with normal ageing and Parkinson’s disease

Abstract: Despite the life-extending success of antiretroviral pharmacotherapy in HIV infection (HIV), the prevalence of mild cognitive impairment in HIV remains high. Near-normal life expectancy invokes an emerging role for age-infection interaction and a potential synergy between immunosenescence and HIV-related health factors, increasing risk of cognitive and motor impairment associated with degradation in corticostriatal circuits. These neural systems are also compromised in Parkinson's disease (PD), which could hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…This would be consistent with the clinical profile of Parkinson's disease (PD), the pathogenesis of which is also associated with degeneration of dopaminergic brain regions. Indeed, a study comparing cognitive and motor deficits in PLWH and adults with PD reported that HIV and PD groups presented with similar deficits in executive function, episodic memory and visual processing, with motor deficits mainly manifesting in PD and not HIV [66].…”
Section: Sleep and Cognition -Role Of Dopaminementioning
confidence: 99%
“…This would be consistent with the clinical profile of Parkinson's disease (PD), the pathogenesis of which is also associated with degeneration of dopaminergic brain regions. Indeed, a study comparing cognitive and motor deficits in PLWH and adults with PD reported that HIV and PD groups presented with similar deficits in executive function, episodic memory and visual processing, with motor deficits mainly manifesting in PD and not HIV [66].…”
Section: Sleep and Cognition -Role Of Dopaminementioning
confidence: 99%
“…Both clinical groups had lower overall current global cognitive scores (DRS-2; Jurica et al, 2004) than the CTL group ( p = .002; Table 1). The neuropsychological profile and clinical motor examination of the three study groups were previously reported in Müller-Oehring, Fama, et al (2021). In brief, both clinical groups had lower EXF and a trend for lower IPS domain scores than CTL, PLWH had lower MEM domain scores than PD and CTL groups, and the PD group performed worse than PLWH and CTL groups on the MOT domain.…”
Section: Resultsmentioning
confidence: 75%
“…The period of recruitment was from 2015 to 2018. Methodology and preliminary data from overlapping study samples were previously reported for frequency-dependent neural activity (Müller-Oehring, Hong, et al, 2021) and cognitive and motor slowing (Müller-Oehring, Fama, et al, 2021; Prabhakar et al, 2020; Sundaram et al, 2019). Written informed consent was obtained from all participants prior to undergoing any study procedures and participants were financially compensated for their time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this study utilized female mice, whereas most MPTP studies are performed in male mice to reduce known variability observed with females. With the advent of ART for HIV-1 treatment, individuals living with HIV have longer lives with fewer co-morbidities, yet still can exhibit motor deficits like PD [176][177][178][179][180]. Thus, a major, yet recurrent question is whether HIV infection affects the development of PD-linked neurodegeneration.…”
Section: Parkinson's Diseasementioning
confidence: 99%